The elusive transformation : science, technology, and the evolution of international politics - Skolnikoff, Eugene B. (Princeton University Press, 1993)
Eugene Skolnikoff treats the roles of science and technology across the entire range of relations among nations, including security and economic issues, environmental questions, international economic competitiveness, the spread of weapons technology, the demise of communism, the new content of dependency relations, and the demanding new problems of national and international governance. He shows how the structure and operation of the scientific and technological enterprises have interacted with international affairs to lead to the dramatic evolution of world politics experienced in this century, particularly after World War II.